Designing a Sovereign Debt Restructuring Mechanism for a European Monetary Fund - George Pavlidis (Intereconomics, 2018)
The establishment of a European Monetary Fund (EMF) enjoys increasing academic and political support, though its advocates do not necessarily agree on the purpose and functions of such an institution. This paper aims to examine the features of the EMF that are relevant to sovereign debt restructuring. We argue that a European sovereign debt restructuring mechanism would be a feasible and useful tool in a crisis. It would facilitate private sector involvement and convey all the advantages that pre-defined procedures offer compared to ad hoc solutions in dealing with a crisis.
Keywords: 330